AI-Supported Video Projects in ESP Classrooms: A Pedagogical Innovation for Business Communication - Asrifan, Andi; Rosmayanti, Vivit; Vargheese, K. J; Vivekanantharasa, Raveenthiran (Journal of English Language Teaching, Linguistics, and Literature Studies, 2025)
The integration of Artificial Intelligence (AI) into English language instruction has created new opportunities for enhancing learner engagement and communication skills, particularly in English for Specific Purposes (ESP) contexts. In Business English courses, students must master professional speaking tasks that require fluency, accuracy, and confidence. However, few studies have explored how AI tools can be combined with project-based learning (PBL) to support these outcomes. This study examines the use of AI-supported video projects to enhance speaking performance and improve learner perceptions in a Business English classroom. Using a mixed-methods design, quantitative data from pre- and post-tests and qualitative reflections were analyzed. Results showed significant gains in speaking performance and increased learner autonomy, confidence, and engagement. Students also encountered several challenges, including technical difficulties in using AI applications and initial anxiety about video recording, which required patience and self-regulation to overcome. Despite these challenges, students viewed the AI tools as beneficial. These findings suggest that integrating AI into PBL tasks can serve as a transformative approach for ESP instruction in higher education.Keywords: Artificial Intelligence in Education; Business English Speaking Skills; English forSpecific Purposes (ESP); Project-Based Learning; Technology-Enhanced LanguageLearning